The Effect of Acute Administration of the Aqueous Calyx Extract of Hibiscus sabdariffa on Blood pressure, Heart rate and Double Product of Apparently Healthy Human Subjects during Different Postures (Nigerian Journal of Physiological Sciences, 2022)
The aqueous calyx extract of Hibiscus sabdariffa (HS) is widely consumed as a beverage in Northern Nigeria and other parts of the world. HS has been reported to lower blood pressure (BP) in animals and man. However, not much is known about the effect of HS on BP in different postures. We tested the hypothesis that HS may lower BP, heart rate (HR) and heart rate-pressure product or double product (DP) by attenuating the discharge of the autonomic nervous system in different postures. Experiments were performed in accordance with the Principles of the Declaration of Helsinki. Following ethical approval and informed consent, BP and HR were measured in different postures (supine, sitting and standing) in apparently healthy human subjects (n=20) before and after (+HS) the oral administration of 15mg/Kg HS. Mean arterial pressure (MAP; taken as representative BP) and DP were calculated. Results are expressed as mean ±SEM. Paired t test and ANOVA with a post hoc Bonferroni test were used for statistical analyses. P